2000
DOI: 10.1111/j.1469-445x.2000.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Filling and Cardiovascular Functional Capacity in Older Men

Abstract: We investigated anaerobic threshold (< èL) gas exchange kinetics and maximal oxygen uptake (ýOµ,max) among older men with reduced left ventricular end-diastolic filling (LVDF). Ten men (mean age, 73 years) with LVDF impairment and low fitness, but without other cardiovascular dysfunction were studied. Treatments compared to control included: 5 days, high intensity exercise training protocol; 5 days, calcium channel blockade (240 mg verapamil); 21 days, detrainingÏwashout; and 5 days, combined treatments. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 37 publications
(55 reference statements)
1
19
2
Order By: Relevance
“…A correlation of 0.87 and 0.91 was observed, respectively. This is similar to previous reports in our laboratory (27,33). Subjects in both groups were stratified further into three groups defined on the basis of age, sex, and achieved METs as previously described (12).…”
Section: Cardiovascular Fitnesssupporting
confidence: 54%
See 2 more Smart Citations
“…A correlation of 0.87 and 0.91 was observed, respectively. This is similar to previous reports in our laboratory (27,33). Subjects in both groups were stratified further into three groups defined on the basis of age, sex, and achieved METs as previously described (12).…”
Section: Cardiovascular Fitnesssupporting
confidence: 54%
“…Individual morbid conditions were combined into the Charlson Comorbidity Index score (32), a prospectively validated weighted index that includes the number and severity of comorbidities. Those in the sedentary group also had simultaneous collection of respired gases during exercise treadmill testing to determine VO 2max (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2ϩ channel blockade, which reduces systolic contractility by decreasing intracellular Ca 2ϩ , reduces IVRT and improves early diastolic filling in older men (27). Thus the increased SЈ in the trained older men might be expected to reduce early diastolic relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results that suggest a strong link between ýOµ,max and FFM may be fortuitous and indirectly the result of changes in blood volume with age. However, in a study of exercise training in the elderly we demonstrated an increase in ýOµ,max that appeared to be due to factors other than the coincident increase in blood volume (Petrella et al 2000). The importance of central cardiovascular limitations might be critical to the ýOµ,max (Rowell, 1993) during younger ages, while muscle oxidative capacity in older less active subjects might be critical (Wagner et al 2000).…”
Section: ----------------------------mentioning
confidence: 91%